2015
DOI: 10.1007/s40808-015-0027-0
|View full text |Cite
|
Sign up to set email alerts
|

Runoff and sediment yield modeling using ANN and support vector machines: a case study from Nepal watershed

Abstract: Physics-based models for simulation of runoff and sediment yield from watersheds are relatively composite model based on learning algorithm. Physics-based is complex model due to involvement of tremendous spatial variability of watershed characteristics and precipitation patterns. Recently, pattern-learning algorithms such as the artificial neural networks (ANNs) have gained recognition in simulating the rainfall-runoff-sediment yield processes producing a comparable accuracy. We have simulated daily runoff an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(18 citation statements)
references
References 52 publications
(54 reference statements)
1
17
0
Order By: Relevance
“…Some different applications are as follows. Prediction of uniaxial compressive strength of travertine rocks ; temperature variations and generate missing temperature data in Iran (Salami and Ehteshami 2016); river flow forecasting (Kasiviswanathan and Sudheer 2016); prediction of water quality index in groundwater systems (Sakizadeh 2016 (Javan et al 2015); runoff and sediment yield modeling (Sharma et al 2015); modeling Secchi disk depth (SD) in river (Heddam 2016b); and predicting phycocyanin (PC) pigment concentration in river (Heddam 2016c).…”
Section: Multilayer Perceptron Neural Network (Mlpnn)mentioning
confidence: 99%
“…Some different applications are as follows. Prediction of uniaxial compressive strength of travertine rocks ; temperature variations and generate missing temperature data in Iran (Salami and Ehteshami 2016); river flow forecasting (Kasiviswanathan and Sudheer 2016); prediction of water quality index in groundwater systems (Sakizadeh 2016 (Javan et al 2015); runoff and sediment yield modeling (Sharma et al 2015); modeling Secchi disk depth (SD) in river (Heddam 2016b); and predicting phycocyanin (PC) pigment concentration in river (Heddam 2016c).…”
Section: Multilayer Perceptron Neural Network (Mlpnn)mentioning
confidence: 99%
“…Determining the appropriate value of these parameters is often a heuristic trial-and-error process [25]. It is shown that an exponentially growing sequence of parameters works better [29].…”
Section: Support Vector Regressionmentioning
confidence: 99%
“…A comparison of the WR model and ANN has shown that the WR model provided better monthly rainfall forecast [9]. Many studies have shown SVR models to be better than ANN models [1,7,20,29]. The WR model decomposes the monthly rainfall time series into detail and approximation components using DWT, and a new time series is generated by adding an approximation component and effective detail components.…”
Section: Introductionmentioning
confidence: 99%
“…Findings from their study presented that the hybrid model helps in making run time substantially quicker with greater accurateness in runoff prediction. Misra et al (2009) and Sharma et al (2015) applied SVM and ANN models for predicting both runoff and sediment concentration of different watersheds. An outcome of SVM was assessed against ANN and simple regression, and it was observed that the SVM model was more competent for predicting runoff and sediment concentration under equivalent prediction accurateness.…”
Section: Introductionmentioning
confidence: 99%